Perovskite crystalline silicon laminated solar cell structure, preparation method and cell
By using an interface modification layer and HCOOK solution in perovskite crystalline silicon stacked solar cells and combined with ICL steam treatment, the performance degradation caused by interface reaction in stacked solar cells is solved, and stability and efficiency are improved.
Patent Information
- Application Number
- CN202411393792.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-10
AI Technical Summary
The interface reaction between different material layers in stacked solar cells leads to a degradation of battery performance. How to improve the stability of stacked solar cells has become an urgent problem.
Using perovskite crystal silicon stacked solar cell structure, by setting an interface modification layer between the perovskite film layer and the hole transport layer, using APC materials to regulate interface interactions, inhibit non-radiative recombination of the interface, and in perovskite HCOOK solution was added to the solution to improve the quality and stability of the film layer, and combined with ICL steam treatment to achieve uniform surface passivation.
It effectively enhances charge transfer, suppresses non-radiated recombination at the interface, improves photoelectric conversion efficiency and battery stability, and extends the module life.
Smart Images

Figure CN119300599A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic cells, and in particular to a perovskite crystalline silicon laminated solar cell structure, a preparation method and a cell. Background Art
[0002] Organic-inorganic hybrid perovskite solar cells have attracted much attention and developed rapidly internationally due to their outstanding advantages such as low cost, easy preparation and excellent photoelectric properties.
[0003] Perovskite is considered to be the next generation of low-cost, high-efficiency photovoltaic materials with the most application prospects. The conversion efficiency of single-junction cells has also increased significantly in recent years. Tandem solar cells are composed of multiple battery units stacked together, which can more fully absorb and utilize solar energy and improve photoelectric conversion efficiency. However, there may be interface reactions between different material layers in tandem solar cells. These reactions may cause the battery performance to deteriorate or fail. Chemical reactions and diffusion at the interface need to be effectively controlled to ensure the stable operation of the battery.
[0004] It can be seen that how to improve the stability of stacked solar cells has become a technical problem that needs to be urgently solved by those skilled in the art. Summary of the invention
[0005] The present invention provides a perovskite crystalline silicon tandem solar cell structure, a preparation method and a battery to improve the stability of the tandem solar cell.
[0006] In order to solve the above technical problems, an embodiment of the present invention provides a perovskite crystalline silicon stacked solar cell structure, including: a first metal electrode layer, a first conductive layer, a first hole transport layer, a first passivation layer, a second passivation layer, a third passivation layer, a first electron transport layer, a second conductive layer, a second hole transport layer, a first interface modification layer, a power generation layer, a second interface modification layer, a second electron transport layer, a third conductive layer, and a second metal electrode layer arranged in sequence from bottom to top.
[0007] The first metal electrode layer is provided on one side of the first conductive layer, and the first hole transport layer is provided on the other side of the first conductive layer; the first hole transport layer is provided on one side of the first passivation layer, and the second passivation layer is provided on the side of the first passivation layer away from the first hole transport layer; the second passivation layer is provided on one side of the third passivation layer, and the first electron transport layer is provided on the side of the third passivation layer away from the second passivation layer; the first electron transport layer is provided on one side of the second conductive layer, and the second hole transport layer is provided on the side of the second conductive layer away from the first electron transport layer; the second hole transport layer is provided on one side of the first interface modification layer, and the power generation layer is provided on the side of the first interface modification layer away from the second hole transport layer; the power generation layer is provided on one side of the second interface modification layer, and the second electron transport layer is provided on the side of the second interface modification layer away from the power generation layer; the second electron transport layer is provided on one side of the third conductive layer, and the second metal electrode layer is provided on the side of the third conductive layer away from the second electron transport layer; wherein the second hole transport layer is prepared from poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], and the second interface modification layer is prepared from 5-aminopyridine-2-carboxylic acid.
[0008] Furthermore, the thickness of the second hole transport layer is 20-30 nm.
[0009] Furthermore, the thickness of the first interface modification layer is 10-20 nm.
[0010] Furthermore, the power generation layer is composed of Cs 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 and potassium formate solution.
[0011] Furthermore, the thickness of the power generation layer is 300-500 nm.
[0012] Furthermore, the second interface modification layer is prepared from 2-aminoethylphosphonic acid.
[0013] Another embodiment of the present invention provides a method for preparing a perovskite crystalline silicon tandem solar cell, which is applied to the perovskite crystalline silicon tandem solar cell structure as described above, comprising:
[0014] An n-type single crystal silicon substrate is used as the second passivation layer, and a hydrogenated intrinsic amorphous silicon layer is deposited on both sides of the second passivation layer as the first passivation layer and the third passivation layer.
[0015] A p-type hydrogen-doped nano-silicon thin film layer is deposited on a side of the first passivation layer away from the second passivation layer by using a very high frequency plasma enhanced chemical vapor deposition method as a first hole transport layer.
[0016] A layer of n-type hydrogen-doped nano-silicon thin film layer is deposited as a first electron transport layer on a side of the third passivation layer away from the second passivation layer by using a very high frequency plasma enhanced chemical vapor deposition method.
[0017] A layer of indium tin oxide film is deposited as a first conductive layer on a side of the first hole transport layer away from the first passivation layer by magnetron sputtering.
[0018] A layer of indium tin oxide film is deposited as the second conductive layer on the side of the first electron transport layer away from the third passivation layer by magnetron sputtering.
[0019] A copper layer is deposited on a side of the first conductive layer away from the first hole transport layer by screen printing as a first metal electrode layer.
[0020] A layer of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] is deposited on the side of the second conductive layer away from the first electron transport layer by a slit coating method as a second hole transport layer.
[0021] A 5-aminopyridine-2-carboxylic acid film layer is deposited on the side of the second hole transport layer away from the second conductive layer by a slit coating method as a first interface modification layer.
[0022] A layer of Cs is deposited on the side of the first interface modification layer away from the second hole transport layer by a doctor blade method. 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The membrane layer serves as a power generation layer.
[0023] The perovskite surface is treated with steam using iodine chloride vapor with a concentration of 5-10%.
[0024] A layer of 2-aminoethylphosphonic acid is deposited on the surface of the power generation layer after steam treatment by a slit coating method as a second interface modification layer.
[0025] A tin dioxide film layer is deposited on the second interface modification layer by thermal evaporation as a second electron transport layer.
[0026] A layer of indium-doped zinc oxide is deposited on the second electron transport layer by magnetron sputtering as the third conductive layer.
[0027] A copper layer is deposited on the third conductive layer by screen printing as a metal electrode layer.
[0028] Furthermore, the n-type single crystal silicon substrate is used as the second passivation layer, and a hydrogenated intrinsic amorphous silicon layer is deposited on both sides of the second passivation layer as the first passivation layer and the third passivation layer, respectively, including:
[0029] An n-type single crystal silicon substrate is used as the second passivation layer, the second passivation layer is textured with potassium hydroxide or sodium hydroxide solution, the textured second passivation layer is cleaned with ozone ultrapure water, and the cleaned second passivation layer is corroded with 35% hydrofluoric acid solution.
[0030] A layer of hydrogenated intrinsic amorphous silicon is deposited on the top surface and the bottom surface of the etched passivation layer by plasma enhanced chemical vapor deposition as the first passivation layer and the third passivation layer respectively.
[0031] Furthermore, a layer of Cs is deposited on the side of the first interface modification layer away from the second hole transport layer by using a doctor blade coating method. 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The membrane layer serves as a power generation layer and includes:
[0032] To a solution of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1, add FAI / FABr / CsI / CsBr / PbI2 / PbBr2 in a molar ratio of 0.48:0.32:0.12:0.08:0.6:0.4, add guanidine tetrafluoroborate, heat and stir at 50°C for 2 hours, and filter with 0.22um polytetrafluoroethylene to obtain a precursor solution.
[0033] Potassium formate solution is added to the precursor solution to obtain a perovskite mixed solution, and the perovskite mixed solution is scraped onto the first interface modification layer to form a Cs 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The membrane layer serves as a power generation layer.
[0034] Another embodiment of the present invention provides a perovskite crystalline silicon tandem solar cell, comprising the above-mentioned perovskite crystalline silicon tandem solar cell structure.
[0035] Compared with the prior art, the embodiments of the present invention have the following advantages:
[0036] (1) The first interface modification layer is prepared using APC material, and the interface between perovskite and PTAA is regulated through multiple bonding interactions, thereby enhancing charge transfer and inhibiting interfacial non-radiative recombination. APC induces uniform adsorption energy of perovskite on the surface of the perovskite film layer, promoting uniform crystallization of perovskite without residual stress. The presence of the APC intermediate layer can also eliminate the phenomenon of local edge states caused by iodine vacancies in the perovskite cell near the edge of the cell conduction band.
[0037] (2) The HCOOK solution added to the perovskite solution used to prepare the power generation layer can improve the quality of the perovskite film without changing the band gap, and can also reduce the defect concentration and thus improve the phase stability. In addition, K cation doping, together with the perovskite cations in the perovskite solution, can improve the quality of the perovskite film and increase the grain size, inhibiting non-radiative recombination and ion migration in the perovskite film. K ions can also effectively passivate defects at the grain boundaries and film surface, inhibiting the hysteresis behavior of the device.
[0038] (3) ICL steam treatment can achieve a uniform surface passivation effect, allowing the entire film to exhibit a long photoluminescence lifetime evenly over a large area, while significantly reducing the defect sources that induce material degradation, thereby achieving a consistent improvement in efficiency and a significant extension of module life within the achievable device area. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 A schematic structural diagram of a perovskite crystalline silicon stacked solar cell structure provided by the present invention;
[0040] Figure 2 It is a structural schematic diagram of a perovskite crystalline silicon stacked solar cell structure provided by one embodiment of the present invention;
[0041] Reference numerals:
[0042] Among them, 1. the first metal electrode layer; 2. the first conductive layer; 3. the first hole transport layer; 4. the first passivation layer; 5. the second passivation layer; 6. the third passivation layer; 7. the first electron transport layer; 8. the second conductive layer; 9. the second hole transport layer; 10. the first interface modification layer; 11. the power generation layer; 12. the second interface modification layer; 13. the second electron transport layer; 14. the third conductive layer; 15. the second metal electrode layer. DETAILED DESCRIPTION
[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] In the description of this application, the terms "first", "second", "third", etc. are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", "third", etc. may explicitly or implicitly include one or more of the feature. In the description of this application, unless otherwise specified, "plurality" means two or more.
[0045] In the description of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be a connection between the two elements. The terms "vertical", "horizontal", "left", "right", "upper", "lower" and similar expressions used herein are only for illustrative purposes, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0046] In the description of this application, it should be noted that, unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood by specific circumstances.
[0047] An embodiment of the present invention provides a perovskite crystalline silicon stacked solar cell structure. For details, see Figure 1 and Figure 2 , Figure 1 A schematic structural diagram of a perovskite crystalline silicon stacked solar cell structure provided by the present invention is shown. Figure 2A schematic structural diagram of a perovskite crystalline silicon tandem solar cell structure provided in one embodiment of the present invention is shown, comprising:
[0048] Arranged from bottom to top are the first metal electrode layer 1, the first conductive layer 2, the first hole transport layer 3, the first passivation layer 4, the second passivation layer 5, the third passivation layer 6, the first electron transport layer 7, the second conductive layer 8, the second hole transport layer 9, the first interface modification layer 10, the power generation layer 11, the second interface modification layer 12, the second electron transport layer 13, the third conductive layer 14, and the second metal electrode layer 15.
[0049] Specifically, Figure 1 and Figure 2 As shown:
[0050] The first metal electrode layer 1 is provided on one side of the first conductive layer 2, and the first hole transport layer 3 is provided on the other side of the first conductive layer 2. The first hole transport layer 3 is provided on one side of the first passivation layer 4, and the second passivation layer 5 is provided on the side of the first passivation layer 4 away from the first hole transport layer 3. The second passivation layer 5 is provided on one side of the third passivation layer 6, and the first electron transport layer 7 is provided on the side of the third passivation layer 6 away from the second passivation layer 5.
[0051] The first metal electrode layer 1 is a copper (Cu) layer with a thickness of 10-100 nm.
[0052] In particular, the first conductive layer 2, the first hole transport layer 3, the first passivation layer 4, the second passivation layer 5, the third passivation layer 6, the first electron transport layer 7 and the second conductive layer 8, the above seven-layer structure together constitutes a HJT (intrinsic thin film heterojunction) battery structure. Specifically, the first conductive layer 2 of this embodiment is an indium tin oxide (ITO) film layer with a thickness of 100 to 250 nm, the first hole transport layer 3 is a p-type hydrogenated intrinsic amorphous silicon (p-nc-Si: H) film layer with a thickness of 5 to 7 nm, and the first passivation layer 6 is a p-type hydrogenated intrinsic amorphous silicon (p-nc-Si: H) film layer with a thickness of 5 to 7 nm. The passivation layer 4 is a hydrogenated intrinsic amorphous silicon layer (ia-Si:H) film layer with a thickness of 3 to 5 nm, the second passivation layer 5 is an n-type single crystal silicon substrate with a thickness of 120 to 150 um, the third passivation layer 6 is a hydrogenated intrinsic amorphous silicon layer (ia-Si:H) film layer with a thickness of 3 to 5 nm, the first electron transport layer 7 is an n-type hydrogenated intrinsic amorphous silicon (n-nc-Si:H) film layer with a thickness of 5 to 7 nm, and the second conductive layer 8 is an indium tin oxide (ITO) film layer with a thickness of 150 to 250 nm.
[0053] The HJT cell structure combines n-type single crystal silicon and amorphous silicon to form a heterojunction, which reduces the recombination rate of carriers, thereby improving the photoelectric conversion efficiency and effectively absorbing and converting solar energy. The hydrogenated intrinsic amorphous silicon film (ia-Si:H) in the HJT cell acts as a buffer layer, which has a good passivation effect on the crystalline silicon surface, reducing surface defects and recombination losses, and further improving the efficiency of the cell.
[0054] One side of the second conductive layer 8 is the first electron transport layer 7 , and the second hole transport layer 9 is disposed on the side of the second conductive layer 8 away from the first electron transport layer 7 .
[0055] Specifically, the second hole transport layer 9 of this embodiment is a poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) film layer with a thickness of 20 to 30 nm. The film layer functions to transport holes generated by the perovskite photovoltaic reaction.
[0056] One side of the first interface modification layer 10 is the second hole transport layer 9 , and the side of the first interface modification layer 10 away from the second hole transport layer 9 is the power generation layer 11 .
[0057] In perovskite solar cells, there is a phenomenon of interfacial non-radiative recombination, where non-radiative recombination means that when electrons and holes recombine in the material, energy is released in the form of heat energy rather than light energy, which will lead to energy loss and reduce battery efficiency. Therefore, this phenomenon needs to be suppressed. This embodiment adopts a method of setting a first interface modification layer between the perovskite film layer and the hole transport layer to suppress interfacial non-radiative recombination.
[0058] The interface between the perovskite film layer and the hole transport layer is one of the key factors that determine the performance of the battery. Specifically, the first interface modification layer 10 of this embodiment is a 5-aminopyridine-2-carboxylic acid (APC) film layer with a thickness of 10 to 20 nm. As an interface modification layer, APC can form multiple bonding interactions with perovskite and PTAA through the amino and carboxyl groups in its molecular structure, regulate the interface between perovskite and PTAA, thereby enhancing charge transfer and inhibiting interface non-radiative recombination, so that the energy barrier that the holes need to overcome to migrate from the perovskite layer to PTAA is reduced, and the migration efficiency is improved. Density functional theory studies have shown that APC induces uniform adsorption energy on the perovskite surface, which means that the adsorption of APC molecules on the perovskite surface is uniform, does not lead to local stress concentration, contributes to the uniform crystallization of perovskite, promotes uniform crystallization without residual stress, and improves the stability and performance of the material.
[0059] In addition, perovskite materials often have some defects, such as iodine vacancies. Iodine vacancies are common defects in perovskite materials. They will form local edge states near the conduction band edge. Local edge states refer to local energy levels formed near the edge of the conduction band or valence band of the material, leading to charge traps and non-radiative recombination. The introduction of APC can fill these iodine vacancies, reduce the formation of local edge states, and inhibit non-radiative recombination, thereby improving the charge transfer efficiency and battery performance, and eliminating the local edge states caused by iodine vacancies near the conduction band edge.
[0060] Perovskite materials are very sensitive to environmental conditions (such as humidity and oxidation). As the first interface modification layer, APC provides a layer of protection for the perovskite film, reducing the impact of external corrosion factors such as moisture and oxygen on the perovskite film, and to a certain extent enhancing the environmental stability of the film, thereby improving the long-term service life of solar cells.
[0061] In the interaction between APC, perovskite and PTAA, the amino group (-NH2) in APC can form coordination bonds with the lead (Pb) atoms on the surface of perovskite, and can also form hydrogen bonds with the nitrogen atoms in PTAA. The carboxyl group (-COOH) can form coordination bonds with the lead atoms on the surface of perovskite, and can also form hydrogen bonds with the carbon atoms in PTAA, thereby guiding the flow of charges.
[0062] These multiple bonding interactions effectively regulate the interface between perovskite and PTAA. APC can form a favorable spatial arrangement, providing a more stable and continuous transmission path for holes. Through its molecular structure, the charge transfer channel between PTAA and the perovskite layer is wider and more efficient, and charges can be transferred more smoothly from the perovskite layer to the PTAA layer, enhancing the charge transfer efficiency. Under light conditions, a built-in electric field is formed at the interface between PTAA and perovskite. The presence of APC can affect the distribution and intensity of this electric field, thereby prompting holes to migrate from the perovskite layer to the PTAA layer faster.
[0063] In addition, the polar functional groups of APC may produce a polarization effect under the action of the electric field, which can enhance the interfacial electric field to a certain extent, thereby increasing the migration speed of charge carriers and further improving the photoelectric conversion efficiency of solar cells.
[0064] One side of the second interface modification layer 12 is the power generation layer 11 , and the side of the second interface modification layer 12 away from the power generation layer 11 is the second electron transport layer 13 .
[0065] The power generation layer is the light absorption layer of the perovskite cell and is the core part of the entire cell. This embodiment uses a perovskite film layer as the power generation layer. Specifically, Cs 0.05 FA 0.67 MA0.33 PbB 1.31 I 1.69 As the preparation material of the power generation layer, the thickness can be set to 300-500nm. In the design of the perovskite composition, a small amount of I defects and MA defects are the source of deep-level electron and hole defects in MAPbI3. Br doped in MAPbI3 has the effect of inhibiting hole defects. MA / FA / Cs can inhibit the appearance of yellow FAPbI3, which will lose the photoelectric effect. The introduction of MA and Cs can relax the stress of the crystal structure and stabilize the a-phase FAPbI3.
[0066] In addition, when preparing the perovskite solution for preparing the power generation layer, adding 1%-2% of the volume of the precursor solution of 1mol% potassium formate (HCOOK) solution to the precursor solution can improve the quality of the perovskite film of the power generation layer without changing the band gap, and also reduce the defect concentration and improve the phase stability. And the K cation doping in the solution, together with the cations in the perovskite component, can improve the quality of the perovskite film and increase the grain size, inhibit the non-radiative recombination and ion migration line in the perovskite film, and the K ions can also effectively passivate the defects of the grain boundary and the film surface, improve the PCE value, and inhibit the hysteresis behavior of the device.
[0067] Specifically, the second interface modification layer 12 of this embodiment is prepared from a bridging molecule 2-aminoethylphosphonic acid (AEP), and the film thickness is 20-30 nm, which can be used to modify the SnO2 / PVSK buried interface in the pin structure PSC.
[0068] For ease of understanding, PSC refers to the inverse perovskite solar cell (PSC). The pin structure is a type of PSC, which refers to the structure type used in the present invention in which the electron transport layer (n-type layer) is placed on the perovskite layer, while the hole transport layer (p-type layer) is located below the perovskite layer. SnO2 (tin dioxide) is often used as an electron transport layer to form a buried interface with the perovskite film layer. This interface is crucial to the performance of the perovskite cell because it directly affects the transmission and recombination of electrons and the stability of the device.
[0069] As a film layer that promotes electron transport in perovskite cells, the electron transport layer has excellent electron mobility and conductivity, can effectively collect and transport photogenerated electrons generated by the perovskite layer, reduce the loss of electrons during the transmission process, thereby improving the photoelectric conversion efficiency, and plays an important role in the realization of battery functions. Specifically, this embodiment uses tin dioxide (SnO2) as the preparation material of the second electron transport layer 13, the film thickness is 20 to 30 nm, and the film layer functions to transport electrons generated by the perovskite photovoltaic reaction.
[0070] One side of the third conductive layer 14 is the second electron transport layer 13 , and the side of the third conductive layer 14 away from the second electron transport layer 13 is the second metal electrode layer 15 .
[0071] Specifically, the material of the third conductive layer 14 of this embodiment is indium-doped zinc oxide (ZnO:In), and the thickness of the conductive layer 14 can be set to 150-200nm. The material of the second metal electrode layer 15 is copper (Cu), and the thickness of the second metal electrode layer 15 can be set to 10-100nm.
[0072] In summary, the present invention uses APC material to prepare the first interface modification layer, and adjusts the interface between perovskite and PTAA through multiple bonding interactions, thereby enhancing charge transfer and inhibiting interface non-radiative recombination. APC induces uniform adsorption energy of perovskite on the surface of the perovskite film layer, promotes uniform crystallization of perovskite without residual stress; the presence of the APC intermediate layer can also eliminate the phenomenon of local edge states caused by iodine vacancies in perovskite cells near the edge of the battery conduction band. The HCOOK solution added to the perovskite solution used to prepare the power generation layer can improve the quality of the perovskite film without changing the band gap, and can also reduce the defect concentration to improve the phase stability. And K cation doping, acting together with the perovskite cations in the perovskite solution, can improve the quality of the perovskite film and increase the grain size, inhibit non-radiative recombination and ion migration in the perovskite film, and K ions can also effectively passivate defects at the grain boundaries and film surfaces, and inhibit the hysteresis behavior of the device. ICL steam treatment can achieve a uniform surface passivation effect, allowing the entire film to uniformly exhibit a long photoluminescence lifetime over a large area, while significantly reducing the defect sources that induce material degradation, thereby achieving a consistent improvement in efficiency and a significant extension of module life within the accessible device area.
[0073] The embodiment of the present invention further provides a method for preparing a perovskite crystalline silicon tandem solar cell, which specifically comprises the following steps:
[0074] S1. Using a 120-150um n-type single crystal silicon substrate as the second passivation layer, depositing a layer of hydrogenated intrinsic amorphous silicon on both sides of the second passivation layer as the first passivation layer and the third passivation layer, specifically comprising:
[0075] S1.1. Use n-type single crystal silicon substrate as the second passivation layer. Use potassium hydroxide or sodium hydroxide solution to texturize the second passivation layer at a corrosion temperature of 70 to 90°C. Then use ozone ultrapure water to clean the texturized second passivation layer, and use 35% hydrofluoric acid solution to corrode the cleaned second passivation layer. The purpose is to form a tiny fuzzy structure on the surface of the silicon wafer by chemical means to reduce reflectivity and increase light absorption.
[0076] S1.2. On the top and bottom surfaces of the corroded passivation layer, a plasma enhanced chemical vapor deposition method (PECVD deposition method) is used. At a plasma excitation radio frequency source of 13.56 MHz, silane (SiH4) and hydrogen (H2) are introduced to deposit a layer of hydrogenated intrinsic amorphous silicon (ia-Si:H) as the first passivation layer and the third passivation layer, respectively. The film layer thickness is 3 to 5 nm. The function of the film layer is to reduce carrier recombination.
[0077] S2. Using very high frequency plasma enhanced chemical vapor deposition (PECVD deposition) at frequencies of 40 MHz, 70 MHz, and 110 MHz, silane (SiH4), hydrogen (H2), and phosphine (PH3) are introduced in sequence to deposit a layer of n-type hydrogen-doped nanosilicon thin film (n-nc-Si:H) as the first electron transport layer on the side of the third passivation layer away from the second passivation layer, and the film thickness is 5 to 7 nm.
[0078] S3. Using very high frequency plasma enhanced chemical vapor deposition (PECVD deposition) at frequencies of 40 MHz, 70 MHz, and 110 MHz, silane (SiH4), hydrogen (H2), and borane (B2H6) are introduced in sequence to deposit a p-type hydrogen-doped nanosilicon thin film layer (p-nc-Si:H) as the first hole transport layer on the side of the first passivation layer away from the second passivation layer. The film thickness is 5 to 7 nm.
[0079] S4. Depositing an indium tin oxide film (ITO) as a first conductive layer on a side of the first hole transport layer away from the first passivation layer by magnetron sputtering, wherein the film thickness is 100 to 250 nm.
[0080] S5. Deposit an indium tin oxide film (ITO) as a second conductive layer on a side of the first electron transport layer away from the third passivation layer by magnetron sputtering, wherein the film thickness is 150-250 nm.
[0081] S6. Depositing a copper layer as a first metal electrode layer on a side of the first conductive layer away from the first hole transport layer by screen printing, wherein the thickness of the copper layer is 10 to 100 nm.
[0082] S7. Deposit a layer of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] as a second hole transport layer on the side of the second conductive layer away from the first electron transport layer by a slit coating method, wherein the film thickness is 20 to 30 nm.
[0083] S8. A 5-aminopyridine-2-carboxylic acid film layer was deposited as the first interface modification layer on the side of the second hole transport layer away from the second conductive layer by a slit coating method, and the film thickness was 10-20 nm. The multifunctional APC regulates the interface between the perovskite film layer and PTAA through multiple bonding interactions, thereby enhancing charge transfer and suppressing interfacial non-radiative recombination. Density functional theory studies have shown that APC induces uniform adsorption energy on the perovskite surface, promoting uniform crystallization without residual stress. In addition, the APC interlayer eliminates the local edge states caused by iodine vacancies near the conduction band edge.
[0084] S9, using a scraping method to deposit a layer of Cs on the side of the first interface modification layer away from the second hole transport layer 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The membrane layer serves as a power generation layer, specifically including:
[0085] N,N-dimethylformamide (DMF, chemical formula: C3H7NO) and dimethyl sulfoxide (DMSO, chemical formula: C2H6OS) are mixed in a volume ratio of 4:1 to form a mixed solution.
[0086] FAI (formamidine hydroiodide, chemical formula CH5IN2), / FABr (formamidine hydrobromide, chemical formula CH5BrN2), CsI (cesium iodide), CsBr (cesium bromide), PbI2 (lead iodide), and PbBr2 (lead bromide) are added to the above mixed solution in a preset molar ratio. Specifically, the preset molar ratio can be 0.48:0.32:0.12:0.08:0.6:0.4.
[0087] Guanidine tetrafluoroborate (GuaBF4) was added to the mixed solution to improve the crystallinity of the perovskite film. The solution was heated at 50°C to accelerate the rate of the chemical reaction so that guanidine tetrafluoroborate reacted more fully with the components in the perovskite solution. The solution was stirred for 2 hours to ensure uniform mixing of the reactants and ensure that they were evenly distributed in the solution, thereby improving the reaction efficiency.
[0088] After completing the heating and stirring work, use 0.22um polytetrafluoroethylene (PTFE) to filter and remove impurities and insolubles produced during the reaction to obtain a relatively pure perovskite solution, providing conditions for the subsequent preparation of high-quality perovskite films.
[0089] A 1 mol% potassium formate (HCOOK) solution is added to the perovskite solution at a volume of 1% to 2% of the perovskite solution to obtain a perovskite mixed solution, and the perovskite mixed solution is scraped onto the first interface modification layer to form a Cs 0.05 FA 0.67 MA0.33 PbB 1.31 I 1.69 The membrane layer serves as a power generation layer, and the thickness of the power generation layer is 300 to 500 nm.
[0090] Potassium formate (HCOOK) solution added to the perovskite solution can improve the quality of the perovskite film in the power generation layer without changing the band gap, and also reduce the defect concentration and improve the phase stability. In addition, the K cation doping in the solution, together with the cations in the perovskite component, can improve the quality of the perovskite film and increase the grain size, inhibit the non-radiative recombination and ion migration line in the perovskite film, and the K ions can also effectively passivate the defects at the grain boundary and the film surface, improve the PCE value, and inhibit the hysteresis behavior of the device.
[0091] S10. Use 5-10% concentration of iodine chloride vapor to steam treat the surface of the power generation layer at a temperature of 60-70°C. ICL vapor treatment achieves a significantly more uniform surface passivation effect, allowing the entire film to uniformly exhibit a long photoluminescence lifetime over a large area, while significantly reducing the defect sources that induce material degradation, thereby achieving a consistent improvement in efficiency and a significant extension of module life in the accessible device area. Compared with the traditional solution treatment method, chlorine vapor treatment achieves a significantly more uniform surface passivation effect, allowing the entire film to uniformly exhibit a long photoluminescence lifetime over a large area, while significantly reducing the defect sources that induce material degradation, thereby achieving a consistent improvement in efficiency and a significant extension of module life in the accessible device area. It can undergo a large-area uniform passivation reaction with the perovskite surface at normal pressure. Unlike liquid-based methods, gas-phase chlorination treatment can achieve a uniform distribution of reactants over the entire film surface, form a stable chemical bond, inhibit the formation of defects and anchor anions near the surface. Since the vapor uniformly passivates the chlorine over a large area of the perovskite surface, inhibiting defect formation energy and ion diffusion, it brings high stability to the solar cell.
[0092] S11. A layer of 2-aminoethylphosphonic acid (AEP) is deposited on the surface of the power generation layer after steam treatment by a slit coating method as a second interface modification layer, and the film thickness is 20 to 30 nm.
[0093] S12. A tin dioxide film layer is deposited on the second interface modification layer by thermal evaporation as a second electron transport layer. The thickness of the film layer is 20 to 30 nm. The function of the film layer is to transport electrons generated by the perovskite photovoltaic reaction.
[0094] S13. Depositing a layer of indium-doped zinc oxide as the third conductive layer on the second electron transport layer by magnetron sputtering, the film thickness being 150 to 200 nm.
[0095] S14. Depositing a copper layer as a metal electrode layer on the third conductive layer by screen printing, with a film thickness of 10 to 100 nm.
[0096] In order to further clearly reflect the structural characteristics of the perovskite tandem solar cell of the present invention, a perovskite crystalline silicon tandem solar cell structure, a preparation method and a battery provided by the present invention are described in detail below in combination with specific embodiments.
[0097] The reagents used in the following examples are all commercially available.
[0098] Embodiment 1:
[0099] (1) Select 130um N-type single crystal silicon as the substrate as the second passivation layer. Use KOH or NaOH to etch the substrate at 80°C, then use ozone ultrapure water to clean it, and then use 35% HF to etch it.
[0100] (2) A layer of hydrogenated intrinsic amorphous silicon is deposited on both sides of the second passivation layer as the first passivation layer and the third passivation layer, respectively, and the thickness of each layer is 4 nm.
[0101] (3) A p-type hydrogen-doped nano-silicon thin film layer is deposited on the side of the first passivation layer away from the second passivation layer by using a very high frequency plasma enhanced chemical vapor deposition method as a first hole transport layer; a n-type hydrogen-doped nano-silicon thin film layer is deposited on the side of the third passivation layer away from the second passivation layer by using a very high frequency plasma enhanced chemical vapor deposition method as a first electron transport layer; the thickness of the first hole transport layer is 6 nm, and the thickness of the first electron transport layer is 6 nm.
[0102] (4) A layer of indium tin oxide film is deposited as a first conductive layer on a side of the first hole transport layer away from the first passivation layer by magnetron sputtering; a layer of indium tin oxide film is deposited as a second conductive layer on a side of the first electron transport layer away from the third passivation layer by magnetron sputtering; the thickness of the first conductive layer is 100 nm, and the thickness of the second conductive layer is 150 nm.
[0103] (5) A copper layer is deposited on a side of the first conductive layer away from the first hole transport layer by screen printing as a first metal electrode layer. The thickness of the first metal electrode layer is 50 nm.
[0104] (6) A layer of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] as a second hole transport layer is deposited on the side of the second conductive layer away from the first electron transport layer by a slit coating method. The thickness of the second hole transport layer is 25 nm.
[0105] (7) A layer of 5-aminopyridine-2-carboxylic acid (APC) film is deposited on the side of the second hole transport layer away from the second conductive layer by a slit coating method as a first interface modification layer. The thickness of the first interface modification layer is 15 nm.
[0106] (8) A layer of Cs was deposited on the side of the first interface modification layer away from the second hole transport layer by a scraping method. 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The membrane layer serves as a power generation layer, wherein the volume proportion of the HCOOK solution in the perovskite solution used to prepare the power generation layer is 1.5%, and the thickness of the power generation layer is 400nm.
[0107] (9) The perovskite surface was treated with 7% iodine chloride vapor.
[0108] (10) A layer of 2-aminoethylphosphonic acid (AEP) is deposited on the surface of the steam-treated power generation layer by a slit coating method as a second interface modification layer. The thickness of the second interface modification layer is 25 nm.
[0109] (11) A tin dioxide film layer is deposited on the second interface modification layer by a thermal evaporation method as a second electron transport layer. The thickness of the second electron transport layer is 25 nm.
[0110] (12) A layer of indium-doped zinc oxide is deposited on the second electron transport layer by magnetron sputtering as the third conductive layer. The thickness of the third conductive layer is 150 nm.
[0111] (13) A copper layer is deposited on the third conductive layer by screen printing as a metal electrode layer. The thickness of the metal electrode layer is 50 nm.
[0112] Embodiment 2:
[0113] A perovskite battery was prepared according to the method of Example 1, except that:
[0114] The thickness of the APC film layer in step (7) can be set to 5nm, 10nm, 20nm, and 25nm. The remaining steps are the same. The APC film layer with a thickness of 15nm is used as a comparative reference example to test the effect of different thicknesses of the first interface modification layer on the photoelectric conversion efficiency.
[0115] Embodiment 3:
[0116] A perovskite battery was prepared according to the method of Example 1, except that:
[0117] The iodine chloride concentration in step (9) can be set to 3%, 5%, 10%, or 13%, and the remaining steps are the same. An iodine chloride concentration of 7% is used as a comparative reference example to test the effects of different concentrations of iodine chloride vapor on the photoelectric conversion efficiency.
[0118] Embodiment 4:
[0119] A perovskite battery was prepared according to the method of Example 1, except that:
[0120] The volume ratio of the HCOOK solution in step (8) can be set to 0.5%, 1%, 2%, and 2.5%. The remaining steps are the same. The HCOOK solution with a volume ratio of 1.5% is used as a comparative reference example to test the effects of solutions with different volume ratios on the photoelectric conversion efficiency.
[0121] Embodiment 5:
[0122] A perovskite battery was prepared according to the method of Example 1, except that:
[0123] The thickness of the AEP film layer in step (10) can be set to 10nm, 20nm, 30nm, or 35nm. The remaining steps are the same. The AEP film layer with a thickness of 25nm is used as a comparative reference example to test the effect of different thicknesses of the second interface modification layer on the photoelectric conversion efficiency.
[0124] Based on the preparation, observation and testing process of Example 1, Example 2, Example 3, Example 4 and Example 5, each example and comparison are shown in Table 1:
[0125] Table 1 Effects of different APC film thickness, iodine chloride concentration, HCOOK solution volume ratio and AEP film thickness on battery performance
[0126]
[0127]
[0128] It can be seen from the results in Table 1 that, by adopting the battery structure of the present invention, the battery photoelectric conversion efficiency of the perovskite battery performance at various film layer thicknesses, solution proportions and steam concentrations in Example 1 is significantly better than the settings of the battery structures and material proportions in Examples 2 to 5, and a higher photoelectric conversion efficiency can be obtained.
[0129] Another embodiment of the present invention provides a perovskite crystalline silicon tandem solar cell, including the above-mentioned perovskite crystalline silicon tandem solar cell structure. The technical means applied by the perovskite crystalline silicon tandem solar cell of the present invention and the technical effects produced correspond to the above-mentioned perovskite crystalline silicon tandem solar cell structure, and can effectively improve the conversion efficiency of the cell compared with the traditional perovskite cell.
[0130] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A perovskite crystalline silicon tandem solar cell structure, characterized in that: The battery comprises a first metal electrode layer, a first conductive layer, a first hole transport layer, a first passivation layer, a second passivation layer, a third passivation layer, a first electron transport layer, a second conductive layer, a second hole transport layer, a first interface modification layer, a power generation layer, a second interface modification layer, a second electron transport layer, a third conductive layer, and a second metal electrode layer, which are arranged in sequence from bottom to top; The first metal electrode layer is provided on one side of the first conductive layer, and the first hole transport layer is provided on the other side of the first conductive layer; the first hole transport layer is provided on one side of the first passivation layer, and the second passivation layer is provided on the side of the first passivation layer away from the first hole transport layer; the second passivation layer is provided on one side of the third passivation layer, and the first electron transport layer is provided on the side of the third passivation layer away from the second passivation layer; the first electron transport layer is provided on one side of the second conductive layer, and the second hole transport layer is provided on the side of the second conductive layer away from the first electron transport layer; the second hole transport layer is provided on one side of the first interface modification layer, and the power generation layer is provided on the side of the first interface modification layer away from the second hole transport layer; the power generation layer is provided on one side of the second interface modification layer, and the second electron transport layer is provided on the side of the second interface modification layer away from the power generation layer; the second electron transport layer is provided on one side of the third conductive layer, and the second metal electrode layer is provided on the side of the third conductive layer away from the second electron transport layer; wherein the second hole transport layer is prepared from poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], and the first interface modification layer is prepared from 5-aminopyridine-2-carboxylic acid.
2. The perovskite crystalline silicon tandem solar cell structure according to claim 1, characterized in that: The thickness of the second hole transport layer is 20-30 nm.
3. The perovskite crystalline silicon tandem solar cell structure according to claim 1, characterized in that: The thickness of the first interface modification layer is 10-20 nm.
4. The perovskite crystalline silicon tandem solar cell structure according to claim 1, characterized in that: The power generation layer is composed of Cs 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 and potassium formate solution.
5. The perovskite crystalline silicon tandem solar cell structure according to claim 4, characterized in that: The thickness of the power generation layer is 300-500 nm.
6. The perovskite crystalline silicon tandem solar cell structure according to claim 1, characterized in that: The second interface modification layer is prepared from 2-aminoethylphosphonic acid.
7. A method for preparing a perovskite crystalline silicon tandem solar cell, characterized in that: The perovskite crystalline silicon tandem solar cell structure as claimed in any one of claims 1 to 6 comprises: An n-type single crystal silicon substrate is used as a second passivation layer, and a hydrogenated intrinsic amorphous silicon layer is deposited on both sides of the second passivation layer as a first passivation layer and a third passivation layer respectively; Depositing a p-type hydrogen-doped nano-silicon thin film layer as a first hole transport layer on a side of the first passivation layer away from the second passivation layer by using a very high frequency plasma enhanced chemical vapor deposition method; Depositing a layer of n-type hydrogen-doped nano-silicon thin film as a first electron transport layer on a side of the third passivation layer away from the second passivation layer by using a very high frequency plasma enhanced chemical vapor deposition method; Depositing an indium tin oxide film as a first conductive layer on a side of the first hole transport layer away from the first passivation layer by magnetron sputtering; Depositing an indium tin oxide film as a second conductive layer on a side of the first electron transport layer away from the third passivation layer by magnetron sputtering; Depositing a copper layer as a first metal electrode layer on a side of the first conductive layer away from the first hole transport layer by screen printing; Depositing a layer of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] as a second hole transport layer on a side of the second conductive layer away from the first electron transport layer by a slit coating method; Depositing a 5-aminopyridine-2-carboxylic acid film layer as a first interface modification layer on a side of the second hole transport layer away from the second conductive layer by a slit coating method; A layer of Cs is deposited on the side of the first interface modification layer away from the second hole transport layer by a doctor blade method. 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The membrane layer serves as a power generation layer; Using 5-10% concentration of iodine chloride vapor to steam treat the surface of the perovskite; A layer of 2-aminoethylphosphonic acid is deposited on the surface of the power generation layer after steam treatment by a slot coating method as a second interface modification layer; Depositing a tin dioxide film as a second electron transport layer on the second interface modification layer by thermal evaporation; Depositing a layer of indium-doped zinc oxide as a third conductive layer on the second electron transport layer by magnetron sputtering; A copper layer is deposited on the third conductive layer by screen printing as a metal electrode layer.
8. The method for preparing a perovskite crystalline silicon tandem solar cell according to claim 7, characterized in that: The method adopts an n-type single crystal silicon substrate as the second passivation layer, and deposits a hydrogenated intrinsic amorphous silicon layer on both sides of the second passivation layer as the first passivation layer and the third passivation layer, respectively, including: Using an n-type single crystal silicon substrate as a second passivation layer, texturing the second passivation layer with a potassium hydroxide or sodium hydroxide solution, cleaning the texturized second passivation layer with ozone ultrapure water, and corroding the cleaned second passivation layer with a 35% hydrofluoric acid solution; A layer of hydrogenated intrinsic amorphous silicon is deposited on the top surface and the bottom surface of the etched passivation layer by plasma enhanced chemical vapor deposition as the first passivation layer and the third passivation layer respectively.
9. The method for preparing a perovskite crystalline silicon tandem solar cell according to claim 7, characterized in that: The method uses a scraping method to deposit a layer of Cs on the side of the first interface modification layer away from the second hole transport layer. 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The membrane layer serves as a power generation layer and includes: In a solution of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1, FAI / FABr / CsI / CsBr / PbI2 / PbBr2 in a molar ratio of 0.48:0.32:0.12:0.08:0.6:0.4 was added, and guanidine tetrafluoroborate was added, and the mixture was heated and stirred at 50°C for 2 hours, and filtered through 0.22um polytetrafluoroethylene to obtain a precursor solution; Potassium formate solution is added to the precursor solution to obtain a perovskite mixed solution, and the perovskite mixed solution is scraped onto the first interface modification layer to form a Cs 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The membrane layer serves as a power generation layer.
10. A perovskite crystalline silicon tandem solar cell, characterized in that: It comprises the perovskite crystalline silicon stacked solar cell structure as described in any one of claims 1 to 6.